Chemical Profiling, Antiproliferative and Antimigratory Capacity of Haberlea rhodopensis Extracts in an In Vitro Platform of Various Human Cancer Cell Lines - Katerina Spyridopoulou; Sotiris Kyriakou; Angeliki Nomikou; Angelos Roupas; Antreas Ermogenous; Katerina Karamanoli; Daniela Moyankova; Dimitar Djilianov; Alex Galanis; Mihalis I. Panayiotidis; Aglaia Pappa (MDPI AG, 2022)
Haberlea rhodopensis is a Balkan endemic plant that belongs to the Gesneriaceae family, and is believed to have medicinal use and health-promoting properties. This study aimed to (i) prepare aqueous (HAE) and ethanolic (HEE) extracts from the leaves of H. rhodopensis from in vitro propagated plants, (ii) screen for their potential antiproliferative and antimigratory activities, and (iii) chemically characterize both HAE and HEE by identifying compounds which may contribute to their observed bioactivity thereby further supporting their potential use in biomedical applications. The antiproliferative activity of both extracts was assessed against six human cancer cell lines by employing the sulforhodamine-B (SRB) assay. HEE was found to be more potent in inhibiting cancer cell growth as compared to HAE. Therefore, HEE's antimigratory effects were further studied in hepatocellular carcinoma (HepG2) and non-small cell lung adenocarcinoma (A459) cell lines as they were among the most sensitive ones to its antiproliferative activity. HEE was found to exert significant antimigratory concentration-dependent effects in both cell lines assessed with the wound healing assay. Chemical characterization by UPLC-MS/MS analysis identified that HEE contains higher levels of flavonoids, phenolic compounds, pigments (chlorophyll-/-b, lycopene, and β-carotene), monoterpenoids, and condensed tannins compared to HAE, while HAE, contains higher levels of soluble protein and sugars. Furthermore, HEE demonstrated remarkable antioxidant activity evaluated by the 2,2-diphenyl-1-picrylhydrazyl (DPPH●), 2,2-azinobis (3-ethyl-benzothiazoline-6-sulfonic acid) (ABTS●+) and ferric reducing/antioxidant power (FRAP) assays. We have obtained comprehensive results highlighting the potential of HEE as a source of bioactive compounds with anticancer properties. Future studies should aim at identifying the chemical constituents responsible for the bioactivities observed, and focus on investigating HEE's effects, in in vivo preclinical cancer models.